Species richness of bat flies and their associations with host bats in a subtropical East Asian region - Emily Shui Kei Poon; Guoling Chen; Hiu Yu Tsang; Chung Tong Shek; Wing Chi Tsui; Huabin Zhao; Benoit Guénard; Simon Yung Wa Sin (Parasites & Vectors, 2023)
Abstract Background Understanding the interactions between bat flies and host bats offer us fundamental insights into the coevolutionary and ecological processes in host-parasite relationships. Here, we investigated the identities, host specificity, and patterns of host association of bat flies in a subtropical region in East Asia, which is an understudied region for bat fly research. Methods We used both morphological characteristics and DNA barcoding to identify the bat fly species found on 11 cavernicolous bat species from five bat families inhabiting Hong Kong. We first determined the phylogenetic relationships among bat fly species. Then, we elucidated the patterns of bat-bat fly associations and calculated the host specificity of each bat fly species. Furthermore, we assembled the mitogenomes of three bat fly species from two families (Nycteribiidae and Streblidae) to contribute to the limited bat fly genetic resources available. Results We examined 641 individuals of bat flies and found 20 species, of which many appeared to be new to science. Species of Nycteribiidae included five Nycteribia spp., three Penicillidia spp., two Phthiridium spp., one Basilia sp., and one species from a hitherto unknown genus, whereas Streblidae included Brachytarsina amboinensis, three Raymondia spp., and four additional Brachytarsina spp. Our bat-bat fly association network shows that certain closely related bat flies within Nycteribiidae and Streblidae only parasitized host bat species that are phylogenetically more closely related. For example, congenerics of Raymondia only parasitized hosts in Rhinolophus and Hipposideros, which are in two closely related families in Rhinolophoidea, but not other distantly related co-roosting species. A wide spectrum of host specificity of these bat fly species was also revealed, with some bat fly species being strictly monoxenous, e.g. nycteribiid Nycteribia sp. A, Phthiridium sp. A, and streblid Raymondia sp. A, while streblid B. amboinensis is polyxenous. Conclusions The bat fly diversity and specificity uncovered in this study have shed light on the complex bat-bat fly ecology in the region, but more bat-parasite association studies are still needed in East Asian regions like China as a huge number of unknown species likely exists. We highly recommend the use of DNA barcoding to support morphological identification to reveal accurate host-ectoparasite relationships for future studies. Graphical Abstract